THE RESPONSE OF 2nd GRADE “SDN 3 SEKARBANYU” TOWARD CREATIVE READING BOOK (CREBO) MEDIA TO ACHIEVE READING SKILLS FOR LEARNING THEME 7 AND SUB THEMES 2 - Riski Nur Fitrayani; Dwi Kameluh Agustina; Sripit Widiastuti (Universitas Islam Balitar, 2020)
Based on research that has been conducted, researchers found that students in grade 2 at “SDN 3 Sekarbanyu” still not effective when the train reading skills due to lack of media support, the necessary media to attract the attention of students so that the students' reading skills more effectively. The purpose of this research are: (1) describes the development process Crebo media, (2) determine student’s response to media Crebo. The method used in this research is qualitative and quantitative approach. This research was descriptive. The research procedure adapted from Borg and Gall in Sugiono (2013). The results of this research indicate Crebo media assessment of the material aspects of obtaining a mean score of 87.7% to the category of